Jeszcze raz w Nibylandii. O polskich przekładach „Piotrusia Pana” Jamesa Matthew Barriego. Rekonesans eseistyczny - Wieczorkiewicz (Michalska), Aleksandra (Wydawnictwo Korporacja ha!art, 2015)
All children, except one, grow up. Among all the masterpieces of global literature for children, this story surely cannot be defined as a fairytale, even though it tells of wondrous events, a remote island, fairies, mermaids and children that are able to fly. A journey to Neverland is a flight on the wings of imagination, covered with golden fairy dust, but once the travellers long for homecoming, they shall never see the island again. Peter Pan Or The Boy Who Would Not Grow Up (1904) was a spectacular success of the Scottish playwright James Matthew Barrie, whose own childhood was far away from idyllic happiness. Seven years after its opening night, the play was adapted by the author into a story for the little ones, but there are many themes and thoughts in the book that are stereotypically not meant for children. The experience of real-life (not making-believe) strongly marked the language and style of Peter Pan. The article focuses on the Polish translations of Peter and Wendy by J.M. Barrie, especially those created by Maciej Słomczyński (Przygody Piotrusia Pana, 2010) and Michał Rusinek (Piotruś Pan i Wendy, 2006). The author of the article analyses selected fragments of the texts and tries to establish a critical comparison between different translation strategies, showing that translator’s work with such a masterpiece is full of both challenges and surprises.
Keywords: books for children in translation; James Matthew Barrie; literary translation; Peter Pan